The Relationship Between Chronic Disease Management Program (Prolanis) for Diabetes Mellitus and Outpatient Visits Diabetes Mellitus Patients at Class C Palembang Hospitals in 2023 - Dicky Permana Putra; Rizma Adlia Syakurah; Haerawati Idris; Rostika Flora; Najmah Najmah; Misnaniarti Misnaniarti (Eduvest - Journal of Universal Studies, 2024)
Diabetes mellitus (DM) is a chronic disease with an increasing prevalence on a global scale, including in Indonesia. However, it is important to note that Indonesia has a robust primary healthcare system, including the JKN program and the promotion of preventive measures regularly implemented at the primary care level. One of the initiatives designed to enhance the quality of life of individuals with diabetes is the Chronic Disease Management Program (Prolanis). Method: A cross-sectional study explored the relationship between the Diabetes Mellitus Chronic Disease Management Program (Prolanis) and outpatient visits for patients with diabetes mellitus at Class C Palembang Hospitals in 2023. The research utilised secondary data derived from various sources, including 5168 health service data of BPJS Kesehatan, previous research, scientific studies, and the interrelationship between eight independent variables. It was then evaluated using the correlation analysis method and multiple logistic regression. Result and Discussion: The results of the study demonstrate a notable correlation between participation in the JKN program pvalue=0.000 < 0.05, utilization of primary healthcare services pvalue=0.000 < 0.05, HbA1C 0.000<0.005 and engagement in physical activity pvalue=0.009 < 0.05 with the Prolanis DM program and outpatient visits for individuals with diabetes at the Class C Palembang Hospitals in 2023. Conclusion: A reduction in the number of outpatient visits was observed among DM sufferers who participated in the Prolanis program actively participate that influenced JKN membership, health facility, HbA1C result and education-physical activity.